A study of biosecurity international instruments in the context of the international sustainable development law principles and in relation to genetically-modified organisms / Marina Abdul Majid - Marina, Abdul Majid (2017)
International biosecurity agreements and initiatives have coexisted disparately reflecting the sectorial approach of management. This approach is no longer feasible because it is unable to deal with an arising biosecurity matter that encroaches across multiple sectors. The purpose of this study is to analyse whether principles of international law from the New Delhi Declaration of Principles of International Law Relating to Sustainable Development, in short International Sustainable Development Law (ISDL) holds the solution in linking different biosecurity sectors and their respective international agreements and initiatives together in the context of genetically modified organisms (GMOs) for coherent management among international organisations. This study is qualitative. The doctrinal research approach applies to determine the status of sustainable development in international law, to the treaties and case laws used in this study through a document and textual analysis. The socio-legal approach is utilised because this study combines the area of law with biosecurity. A content analysis applies to secondary resources. The provisions of the Cartagena Protocol on Biosafety (CPB), Biological Weapons Convention (BWC), International Health Regulations 2005 (IHR 2005), the World Health Organisation’s (WHO’s) laboratory biosecurity and biopharming initiatives are examined to detect the existence of explicit and implicit elements of ISDL principles. The results from this study indicate that the CPB, BWC, IHR 2005 all reflect the principle of integration in enabling cooperation with other international organisations while collaboration depends on the political will of states. This study found that most of the principles of ISDL have directly been reflected in the CPB and IHR 2005 while indirectly embedded in the BWC. For the BWC, a United Nations (UN) resolution has prescribed the adoption of ISDL principles in the Delhi Declaration. This study’s contribution to the scopus of knowledge is through offering an international law approach utilising ISDL principles in uniting the disparate sectors of international biosecurity agreements and initiatives. This complements the holistic biosecurity definition being proposed in uniting various sectors with a UN coordinating mechanism bringing biosecurity international organisations and agencies together. The findings of the BWC as a biosecurity international arms control agreement achieving the goal of sustainable development contribute to the sparse literature linking international arms control and sustainable development law. This also challenges the understanding of ISDL being limited to international environmental, economic and social law. This study also found that the WHO’s laboratory biosecurity and biopharming initiatives are related to the CPB and BWC through the principle of integration. Elaboration of the IHR 2005, laboratory biosecurity and biopharming initiatives also significantly contribute towards the current scholarly literature of international health and sustainable development law.